Factors related to students' learning motivation at the Aceh Ministry of Health Polytechnic, Tapaktuan Nursing Study Program, South Aceh Regency - Rahmi, Cut; Rasima, Rasima; Lizam, T. Cut; Syamirwan, Syamirwan; Susanti, Susanti (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Learning motivation is an impulse that arises both from within and outside the student, which can generate enthusiasm and enthusiasm for learning and provide direction to learning activities so that the desired goals can be achieved. Educators need to understand the importance of the role of motivation in the learning process so that they can carry out various forms of action or assistance to students. This study aims to identify factors related to learning motivation among students at the Aceh Ministry of Health Polytechnic, Tapaktuan nursing study program, South Aceh Regency. This type of research is descriptive correlative research with a cross-sectional study approach. The study used total sampling to select the research sample. The subjects of this research were 172 students at level I, level II, and level III of the Aceh Ministry of Health Polytechnic, Tapaktuan Nursing Study Program, South Aceh Regency. The data collection technique in the research used a questionnaire and data analysis was carried out using univariate and bivariate analysis with the chi-square statistical test. The results were obtained namely, there is a relationship between interest factors (p-value 0.005), family environment (p-value 0.002), and school environment (p-value 0.005) with student learning motivation and there is no relationship between expectation factors and student learning motivation at the Aceh Ministry of Health Polytechnic, Tapaktuan Nursing Prode, South Aceh Regency with a P value of 0.018.